PENGARUH KONFLIK KERJA DAN STRES KERJA MELALUI KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT DASA WINDU AGUNG - Ria Marginingsih; Kristiana Kristiana (LP2M Universitas Bina Bangsa, 2022)
The purpose of this study was to determine the effect of work conflict and work stress through organizational commitment on employee performance at PT Dasa Windu Agung. The research method used by the author is descriptive. This research was conducted at PT Dasa Windu Agung. The research sample is the employees of PT Dasa Windu Agung as many as 84 people. Data analysis using SEM (Structural Equation Modeling) with SmartPLS (Smart Prtial Least Square) software version 3.0. The results showed that work conflict and work stress were directly and positively related to organizational commitment, then organizational commitment had a positive effect on employee performance. The results of this study also indicate that work conflict and work stress have a positive effect on employee performance through organizational commitment.